Intercultural Negotiation as a Strategic Mechanism in Balancing Global Standardization and Local Adaptation: A Case Study of Tokyo Disneyland - Ardella Febri Dwi Syaharani; Bela Maulana; Yulita Diva; Dian Prihardini Wibawa (LP3M INSTITUT KH YAZID KARIMULLAH, 2026)
The expansion of multinational corporations into culturally diverse markets requires strategic mechanisms capable of balancing global standardization with local adaptation. Intercultural negotiation has increasingly been recognized not only as a communicative process but also as an organizational strategy shaping collaborative structures and operational practices. This article examines the management of Tokyo Disneyland as a unique case of cross-cultural partnership between The Walt Disney Company and Oriental Land Company, where global brand control coexists with local operational autonomy. Using a qualitative case study approach based on secondary data from corporate reports, official documents, and academic literature, the analysis identifies patterns of negotiation embedded in role division, policy formulation, and service delivery. The findings indicate that negotiation outcomes are reflected in selective cultural adaptations, including localized services, products, and communication practices, while maintaining core brand identity. These results highlight that effective intercultural negotiation operates at both structural and operational levels, enabling long-term collaboration and high organizational performance. The article contributes to international management literature by positioning intercultural negotiation as a strategic framework integrating global consistency and local responsiveness in multinational contexts.